2017
DOI: 10.1038/srep45292
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Size and Surface Charge of Gold Nanoparticles on their Skin Permeability: A Molecular Dynamics Study

Abstract: Molecular level understanding of permeation of nanoparticles through human skin establishes the basis for development of novel transdermal drug delivery systems and design and formulation of cosmetics. Recent experiments suggest that surface coated nano-sized gold nanoparticles (AuNPs) can penetrate the rat and human skin. However, the mechanisms by which these AuNPs penetrate are not well understood. In this study, we have carried out coarse grained molecular dynamics simulations to explore the permeation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
138
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(150 citation statements)
references
References 60 publications
6
138
0
1
Order By: Relevance
“…For example, sunscreens containing ZnONPs and TiO 2 NPs are effective barriers against ultraviolet light (UV-light) damage to skin and do not leave white or other residues on the skin [131,132]. AgNPs are used in toothpaste and soap and other cleaning products to achieve an antibacterial effect, and gold nanoparticles (AuNPs) are commonly used as carriers that easily penetrate the skin [132][133][134]. However, the diversity of NMs applied in cosmetics has raised concerns about their potential risks.…”
Section: Zno Nanoparticles-induced Toxicity and The Possible Role Of mentioning
confidence: 99%
“…For example, sunscreens containing ZnONPs and TiO 2 NPs are effective barriers against ultraviolet light (UV-light) damage to skin and do not leave white or other residues on the skin [131,132]. AgNPs are used in toothpaste and soap and other cleaning products to achieve an antibacterial effect, and gold nanoparticles (AuNPs) are commonly used as carriers that easily penetrate the skin [132][133][134]. However, the diversity of NMs applied in cosmetics has raised concerns about their potential risks.…”
Section: Zno Nanoparticles-induced Toxicity and The Possible Role Of mentioning
confidence: 99%
“…They reported that topically applied siRNA‐coated AuNPs could be successfully employed for gene regulation . Moreover, our group among others has systematically studied the interactions of functionalized gold nanoparticles with healthy and damaged skin tissue and found that size, surface charge, as well as functional ligands on nanoparticles play key roles in penetration and interactions of nanoparticles with skin …”
Section: Introductionmentioning
confidence: 99%
“…These mechanisms have even been studied by molecular dynamics simulations. These novel studies have provided a huge opportunity to create nanoparticles for use in the cosmetic field and for transdermal drug delivery [135]. Recently, the photothermal-based antibacterial activity of gold nanorods (AuNRs) coated with cholesterol-PEG and phospholipid-PEG were tested on human skin.…”
Section: Antibacterialmentioning
confidence: 99%